Analisis Usulan Strategi dalam merespon PMK 48/2023: Studi Kasus pada Perusahaan Perhiasan Emas - Angeline, Dian; Hermawan, Ancella Anitawati (E-Jurnal Akuntansi, 2024)
The issuance of PMK 48 in May 2023 concerning taxes on the sales/delivery of gold jewelry, has caused changes in the gold jewelry market in Indonesia. Gold jewelry companies must look for alternative strategies to overcome the impact of these changes. This research aims to analyze alternative proposed strategies that can be used by PT ABC, as a gold jewelry company in Indonesia. This research uses primary data (semi-structured interviews) and secondary data (information from PT ABC reports). The results of this research provide proposed new strategies for PT ABC based on the resources it has. Companies must be agile in creating emergent strategies to face the changes due to external factors. Keywords: PMK 48/2023; gold jewelry; emergent strategy; resource-based theory.